BENANG KUSUT FIQH WARIA (ANALISIS KRITIS TERHADAP POLEMIK IDENTITAS WARIA DALAM ISLAM) - Muiz, Abdul (Universitas Nurul Jadid, 2015)
The main problem the most of religionist until now are still looking the transgender as opponents of the providence of God. They are considered as opponent of destiny because God only created male and female, not transgender. For this reason, transgender is not recognized by religion (God) and must be removed or sequestered. There are several fatwas about the prohibition of transgender in religion. Similarly, the Islamic jurisprudence, transgender in islamic jurisprudence (fiqh) is still not much be touched by ulama. The laws of the transgender that exist today generally do not smoop down on the transgender existence actually. Islam has identified that there are a men who have no sexual desire for women that called ghair ulil irbah min al-rijal. In a hadith someone like that are called mukhannats. About this mukhannats, Ibn Hajar divides the two; min ashlil khilqah (created by God) and bil qashdi (deliberate by human). Moreover Ibn Hajar said that Islam merely forbids the mukhannats who deliberately do it. While those who did indeed original creation only directed to trying to change his personality. Similarly with Ibn Hajar, al-Nawawi also divides the mukhannats into two part; min khalqin (given) and bitakallufin (constucted).